PWE-171 Assessing The Utility Of Key Mri Parameters In Characterising The Mode Of Action Of A Proven Effective Laxative, Ispaghula. (9th June 2014) - Murray, K; Marciani, L; Major, G; Hoad, C; Cox, E; Silos-Santiago, A; Kurtz, C; Kaviani, M; Paul, JA; Gowland, P; Johnston, J; Spiller, R
Abstract : Introduction: Half of the patients who suffer from chronic constipation are dissatisfied with their treatments, which has initiated a recent surge in novel treatments. Assessing the efficacy of these treatments requires techniques that are patient acceptable and non-invasive and allow characterisation of the underlying mode of action. This study assessed the utility of key parameters likely to give insight into laxatives' mode of action including: colonic volumes, transit, ascending colon water content (ACWC) and small bowel water content (SBWC) by means of a randomised double-blind, placebo-controlled, crossover study (RCT) of a known effective laxative, ispaghula. Methods: 16 healthy volunteers (24 ± 4 years old, BMI 23 ± 4 kg m -2 ) participated in this three-way RCT. They took either 21 g/day of ispaghula, 10.5 g/day of ispaghula or a placebo daily on days 1–6. On day 5 they swallowed 5 transit marker pills (TMP) filled with a dilute MR contrast agent and on day 6 were scanned serially for 7 h. The TMPs were assigned a weighted average position score (WAPS) based on their location in the bowel. Protocol compliance was assessed and 9 subjects were included in the per protocol analysis. Results: (mean AUC±SEM, n = 9) Relative to the placebo, 21 g/day but not 10.5 g/day of ispaghula increased the ACWC (Figure 1 ) significantly (11 ± 4 L.min vs. 1.0 ± 0.5 L.min, p < 0.001), while SBWC (Figure 2 ) was increased significantly by both doses (68 ± 15 L.min vs placebo 25 ± 6 L.min, p= < 0.01), and (49 ± 11 L.min, p= < 0.05) respectively. Both doses significantly increased the total colon volume, and there was a significant increase in colon volume at fasted baseline measurement. Ascending colon T1 was also increased by the 21 g/day dose (p < 0.01), but 24 h WAPS for transit were not significantly changed by treatment. Conclusion: The volume of water in both the ascending colon and the small bowel are significantly increased by ispaghula and could be useful biomarkers of a laxative effect. Ispaghula also increased colonic volumes and ascending colon T1 without altering transit times, suggesting it or its metabolites does not stimulate motility. These MRI methods could be readily used in assessing the mode of action of a range of novel agents in constipated patients will provide unique information on the mechanisms of action. Disclosure of Interest: None Declared.